Application of TRPS1 in ER-negative or low expression distant metastatic breast carcinoma - Runze Zhang; Jing Liu; Lei Jiang; Zhiqiang Lang (Pathology and Oncology Research, 2025)
PurposeTraditional markers have various limitations in recognizing the breast origin of distant metastatic breast carcinoma (DMBC), especially in ER-negative or low expression cases. In recent years, TRPS1 has been reported as a breast marker with satisfactory sensitivity and specificity in triple-negative breast cancers (TNBC). We aimed to compare the expression of TRPS1, GATA3, and GCDFP-15 in ER-negative or low-ER-expressing DMBC, and to further evaluate the diagnostic value of TRPS1.MethodsImmunohistochemical staining for TRPS1, GATA3, and GCDFP-15 was performed in 107 cases of ER-negative or low expression DMBC specimens. Nuclear staining was considered positive for TRPS1 and GATA3, and cytoplasmic staining was considered positive for GCDFP-15.ResultsThe positive rates for TRPS1, GATA3, and GCDFP-15 were 90.65% (97/107), 91.59% (98/107), and 42.99% (46/107), respectively. There was no significant difference in the expression rate and intensity between the first two markers (p = 0.929), but both rates were significantly higher than that of GCDFP-15 (p < 0.05). Among these, 6 cases showed positive expression for TRPS1 while GATA3 and GCDFP-15 were negative; 8 cases showed positive expression for GATA3 while TRPS1 and GCDFP-15 were negative.ConclusionTRPS1 is as effective as GATA3 in confirming breast origin for ER-negative or low expression DMBC, and the two markers exhibit excellent complementary effects, both outperforming GCDFP-15. The combined application of TRPS1 and GATA3 is the optimal method to confirm that ER-negative or low-expression distant metastatic carcinoma originates from the breast.